Analysis of geographical distribution and seroepidemiological characterization of leptospirosis in cattle slaughtered of Southwest Goiás slaughterhouses, Brazil (Research, Society and Development, 2020)
Leptospirosis is widespread throughout the world. In the bovine species, economic losses are mainly associated with reproductive failures. Due to its importance, the objective of the work was to determine the serovarieties most related to bovine leptospirosis in southwest Goiás, Brazil. 2,006 samples were collected in two slaughterhouses in 14 of the 18 municipalities in that region. For the diagnosis, the blood serum samples were submitted to the Microscopic Soroagglutination test (SAM), against 32 serovarieties of leptospires, adopting a positive titer greater than 100. A geographical distribution of the positive animals and the main serovarities present in the southwest of Goiás was carried out, and also a questionnaire with the producers, containing epidemiological information, the vaccine being one of the prophylactic measures related to the infection, on the other hand it was also observed that vaccinated animals they have also been shown to be reactive. It was noted 1,406 (70.1%) cattle were seroreactive for at least one of the 32 serovarieties of Lepstospira ssp. tested. The most frequent serovarieties were Guaricura (30.80%), Wolffi (30.51%), Shermani (9.39%), Hardjo (7.54%), Bananal (4.27%) and Pomona (3.27) %). Serranópolis (77.9%), Perolândia (75.5%), Caiapônia (74.7%) and Jataí (73.2%) are the municipalities with the highest frequency of seroreagent animals. Through this research, a high index of seroreactive animals from the studied region was demonstrated, reinforcing the importance of leptospirosis infection in the Southwest region of the State, being necessary, therefore, the implementation of general measures of control and infection of the animals.